Analisis Putusan Pengadilan Agama Bekasi Tentang Pengesahan Nikah Orang Tua Yang Telah Meninggal - Muhammad Syar’i Ramadhoni; Ahmad Rifki; Dewo Prasetiyo; Mastawiyah (Jurnal Teologi Islam, 2026)
Decision Number 1953/Pdt.G/2025/PA.Bks at the Bekasi Religious Court discusses a marriage isbat petition filed by Asmalih bin Matal Siman against his siblings, Asmat bin Matal Siman and Halimah binti Matal Siman, regarding the validation of their parents’ marriage, namely the late Matal Siman bin Siman and the late Asmaroh binti Jaya, which was conducted on January 10, 1963, in accordance with Islamic law but was not registered at the Office of Religious Affairs (KUA) of West Bekasi District. This petition was submitted based on the need for legal administrative purposes and certainty of heir status due to the absence of official marriage registration. This research aims to analyze the legal considerations of the panel of judges in granting the petition and its implications for the validity of unregistered marriages. The research method employs a normative juridical approach by examining the court decision and relevant statutory provisions. The results show that the panel of judges considered that the marriage of the deceased fulfilled the pillars and requirements of marriage under Islamic law, was validly conducted with a guardian and witnesses, and had never been legally challenged. The legal considerations were based on Article 7 of the Compilation of Islamic Law and Article 49 of Law Number 7 of 1989 concerning Religious Courts and its amendments, thereby granting the court jurisdiction to adjudicate the case. The final judgment granted the Petitioner’s request, declared the marriage valid, and imposed court fees of IDR 302,000.00.